Testosterone is Key to Increase the Muscle Capillary Density of Old and Trained Rats - Krause Neto, Walter; Silva, Wellington de Assis; Silva, Amanda dos Santos da; Ciena, Adriano Polican; Souza, Romeu Rodrigues de; Carbone, Patricia Oliva; Anaruma, Carlos Alberto; Gama, Eliane Florencio (Journal of Morphological Sciences, 2019)
Introduction It is indicated that aging reduces muscular vascularity. Thus, strategies that aim to reverse or decrease the progression of these changes are suggested. Therefore, the present study aimed to analyze the blood capillary density of the plantaris muscle (PL) of aged rats submitted to strength training and exogenous testosterone use.Methods A total of 30 rats were divided equally into the following groups: EA: 20 months old; OLD: 24 months old; OLD + S: testosterone; ST: strength training; and ST + S: strength training + testosterone. Strength training was performed 3 times a week for 15 weeks. Testosterone administration was performed by the intraperitoneal method 2 times a week at a dose of 10mg/kg. All of the morphological parameters were analyzed using morphoquantitative techniques.Results A significant increase in the capillaries numerical density of the OLD + S and ST + S groups. The OLD + S and ST + S groups demonstrated a higher ratio of capillaries per myofiber than the EA, OLD and ST groups. The OLD and ST groups had a higher ratio than the EA group. The OLD + S, ST and ST + S groups presented a statistically significant increase in the cross-sectional area in the type I fibers when compared with the EA and OLD groups. However, the ST group showed a significant increase compared with the OLD group. In type II fibers, the ST and ST + S groups showed a greater cross-sectional area than the EA group. As for the mean cross-sectional area, the ST and ST + S groups presented significantly larger areas than the other groups.Conclusion Anabolic steroid administration is crucial to increase the blood capillary density of the plantaris muscle of old rats, independently of the effects of strength training.
Keywords: aging; blood vessels; skeletal muscle; training; steroids